PERAN LIKUIDITAS, PROFITABILITAS DAN SOLVABILITAS DALAM MENGHADAPI POTENSI KEBANGKRUTAN PT TELKOM INDONESIA - Aisy, Rihadatul; Subhan, M. Nuruddin; Kurniawati, Dewi (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2024)
This thesis aims to analyze the role of liquidity, profitability and solvency in facing the potential bankruptcy of PT Telkom Indonesia. The sample in this study uses financial data from PT Telkom Indonesia for 2020-2023 to determine the extent to which these factors influence the company's ability to overcome bankruptcy risk. The analysis techniques used are classical assumption testing and hypothesis testing. The results of this research show that liquidity (Current Ratio) has an effect on the potential for bankruptcy, while profitability (Return on Equity) and solvency (Debt to Asset Ratio) have no effect on the potential for bankruptcy of PT Telkom Indonesia. And simultaneously liquidity (Current Ratio), profitability (Return on Equity) and solvency (Debt to Asset Ratio) together have no effect on the potential bankruptcy of PT Telkom Indonesia.